2006
DOI: 10.4028/www.scientific.net/amr.11-12.631
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic-Organic Thin-Layers which Transform Bio-Molecule Binding into Visible Color Change

Abstract: SiO2 thin-films were prepared by thermal oxidation method. It showed uniform color based on the thin-film interference of visible light. Then we made biotin antenna on the top of SiO2 thin-film. Biotin is one of the vitamins and it has high association constant with protein avidin. After immersed the substrate into avidin solution, certain color changes based on the self-assembling of avidin on its surface were observed. By the immersing these substrates into mono-dispersed polystyrene particle solution, a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Previously, we have demonstrated that a silica thin-film constructed on a silicon substrate showed interference color change when bacteria and protein adsorbed on it. [13][14][15][16] Adsorption of bacteria of a sub-micron scale gave a visible color change, which was not only observed by spectrum measurement, but was also seen by the naked eye. On the other hand, adsorption of small molecules on the nanometre scale, such as antigens and peptides, gave little color change, which was only observed by spectrum measurement.…”
mentioning
confidence: 99%
“…Previously, we have demonstrated that a silica thin-film constructed on a silicon substrate showed interference color change when bacteria and protein adsorbed on it. [13][14][15][16] Adsorption of bacteria of a sub-micron scale gave a visible color change, which was not only observed by spectrum measurement, but was also seen by the naked eye. On the other hand, adsorption of small molecules on the nanometre scale, such as antigens and peptides, gave little color change, which was only observed by spectrum measurement.…”
mentioning
confidence: 99%
“…In fact, we can calculate the whole thickness of the external layer including the layers of oxide (SiO 2 ), organic layers, and microbe. Strong shifts in optical properties were similarly observed when increasing the thickness by the addition of nanolayers [ 3 ], chemical vapor absorption [ 6 , 32 ], and an aqueous dispersion of microgel [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, colorimetric detection systems have a fundamental problem detecting specific molecular interactions, such as antibodies or nucleic acids. At the same time, the advantage of the optical platform is that the unaided eye can detect changes in the iridescent color due to several factors such as the nano-ordered film thickness, the number of layers, and the angle of the incident light [ 3 , 4 , 5 , 6 , 7 ]. The chip presented herein is developed especially for the detection of a specific pathogen, Sphingobium yanoikuyae [ 8 , 9 ], which alters the taste of non-beverage alcohols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation